Identifikasi Potensi Ekonomi Kabupaten dan Kota di Provinsi Banten Tahun 2016-2020 - Marisa Herawati (UNISBA Press, 2022)
This study of background overshadow by existence of pre-eminent economic potency phenomenon and also area classification of regency/Town in Province of Banten not yet been identified to be exploited in an optimal for the development of development. This study aims to identify and analyze potential sectors, which have competitive competitiveness and specialization in each Regency/City. The data used in this study is secondary data for the period 2016-2020 sourced from the Provincial BPS, Regency/City BPS, and Banten Province Bappeda. The analytical model used is LQ Analysis, Growth Ratio Model (MRP), and Overlay Analysis. The results of this study conclude that districts/cities have their respective potentials according to their conditions. The sectors that are mostly owned by regencies/cities in Banten Province are Education Services which are spread over five regencies/cities. Agriculture, Forestry, and Fisheries Sector; Processing industry; Provision of Accommodation and Food and Drink; and Government Administration, Defense, and Mandatory Social Security which are the basic sectors for four of the eight districts/cities in Banten Province. Penelitian ini dilatarbelakangi dengan adanya fenomena potensi ekonomi potensial ditiap daerah Kabupaten/Kota di Provinsi Banten yang belum teridentifikasi dan dimanfaatkan secara optimal untuk pengembangan pembangunan. Penelitian ini bertujuan untuk mengetahui dan menganalisis sektor-sektor potensial, yang mempunyai daya saing kompetitif dan spesialisasi di masing-masing Kabupaten/Kota. Data yang terpakai dalam penelitian ini adalah data sekunder kurun waktu tahun 2016-2020 bersumber dari BPS Provinsi, BPS Kabupaten/Kota, serta Bappeda Provinsi Banten. Model analisis yang digunakan yakni Analisis LQ, Model Rasio Pertumbuhan (MRP), serta Analisis Overlay. Hasil penelitian ini menyimpulkan bahwa kabupaten/kota mempunyai potensi masing-masing sesuai dengan kondisinya. Sektor-sektor yang paling banyak dimiliki oleh kabupaten/kota di Provinsi Banten adalah Jasa Pendidikan yang tersebar di lima kabupaten/kota. Sektor Pertanian, Kehutanan, dan Perikanan; Industri Pengolahan; Penyediaan Akomodasi dan Makan Minum; serta Administrasi Pemerintahan, Pertahanan, dan Jaminan Sosial Wajib yang merupakan sektor basis bagi empat dari delapan kabupaten/kota di Provinsi Banten.